Effect of pH and Fulvic Acid on the Sorption and Diffusion of Europium Ions in Compacted Bentonite as Studied by the Capillary Method - X. Wang; C. Chen; S. Yu; X. Zhou; D. Xu; A. Ren (Adsorption Science & Technology)
The effect of pH and fulvic acid on the diffusion and sorption of Eu(III) ions in compacted bentonite (ρ b = 1120 ± 20 kg/m 3 ) was studied via an “in-diffusion” method at an ionic strength of 0.1 M NaClO 4 . The results (K d values derived from the first slice and theoretical calculations, apparent and effective diffusion coefficients, i.e. D a and D e ) derived from the capillary method were in good agreement with data obtained under similar conditions quoted in the literature and indicated that the diffusion and sorption of Eu(III) ions in compacted bentonite was dependent on the pH value. In the presence of fulvic acid (FA), Eu III –FA complexes were formed at the surface of the compacted bentonite. Hence, the presence of FA led to a reduction in the diffusion of Eu(III) ions in compacted bentonite. It may be concluded that humic substances act as a significant sink for Eu(III) ions in compacted bentonite. The value of D a derived experimentally was used to simulate the diffusion of Eu(III) ions in compacted bentonite, the results indicating that several metres of compacted bentonite would be sufficient to prevent the diffusion of Eu(III) ions from a repository to the natural environment.